2021
DOI: 10.3390/su13073842
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Factors Influencing Farmers’ Adoption of Organic Farming

Abstract: Understanding the evidence-based factors that influence the adoption of organic farming yields benefits in terms of managing said adoption effectively. We searched relevant articles published in databases including Web of Science, Scopus, PubMed, Google Scholar, and Google. The inclusion criteria were as follows: original article; published in journals, proceedings, or dissertations; full article publication; published between 1999 and 2021; focusing on assessing the adoption of organic farming or conversion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 41 publications
(238 reference statements)
2
53
0
1
Order By: Relevance
“…(3) attitudinal or psychological factors; and (4) social capital and learning. A similar categorization of the evidence-based factors affecting farmers' organic farming adoption decision can be found in the most recent reviews, e.g., [1].…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…(3) attitudinal or psychological factors; and (4) social capital and learning. A similar categorization of the evidence-based factors affecting farmers' organic farming adoption decision can be found in the most recent reviews, e.g., [1].…”
Section: Introductionmentioning
confidence: 86%
“…Most of the extant research found the probability of organic farming adoption is higher for farmers with higher educational levels, e.g., [4,5,8]. The two recent review articles, [1,12], also suggested the same conclusion after a systematic review. However, in some study of West Africa, farmers with lower educational levels were found be more inclined to adopting organic cotton farming practices [10], while the effect of education was found to be insignificant in explaining the adoption of organic horticultural techniques in the UK [3].…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations